PEMANFAATAN RUANG PUBLIK DI KAMPUNG ALUN-ALUN KOTAGEDE, YOGYAKARTA (Ditinjau dari Seting Fisik dan Seting Aktivitas) - , WIRA KARTIKA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Kampung Alun alun is crowded housing area in Yogyakarta. The comfortable and useful public space availability is rarely found in the crowded urban area. The research took the public space theme in Kampung Alun alun, Kotagede, Yogyakarta. It explored how the useable public space and what factors influence the public space use. The interesting things in Kampung Alun alun were the public consciousness of providing the public space by allowing the private open space to be used by public as a public space. Furthermore, the traditional public cultures have been being preserved well, such as there were some javanese traditional buildings until now. Those become to be learned further.The research method was rasionalistic qualitative by taking five cases. The first step was deduction proccess by grouping the cases due to its variables and using matrix or tables to categorize. Further, the relation of the variables of the cases were sincronized. The results were interpretized as public space characters and the factors influencing the public space use. The research analization was done inductively based on the cases to find the pattern of the cases. The datas were consisted of phisical setting and activity setting. After analizing, it concluded there was correlation of physical setting factors such as orientation, border, shape, size, condition and the component of reasonable or attraction factors (place of destination). The activity setting was consisted of activity type, activity pattern, time of activity, ages and gender of the users as a stimulant (place of origin). The usable factors of public space in Kampung Alun alun were influenced by the width of space, amenities of the space and the users intimate.